2003
DOI: 10.1580/1080-6032(2003)014[0078:hpicay]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Poisoning in Children: A 5-Year Retrospective Study

Abstract: 1) There is a higher risk of hydrocarbon poisoning during the hot months of the year; 2) the respiratory system is the main target organ affected; 3) pneumonia is in most cases interstitial and bilateral; 4) vomiting after hydrocarbon ingestion is related to the rate of development of pneumonia; 5) symptoms of CNS impairment were correlated with hypoxemia, pneumonia, and fever; and 6) CNS toxicity may occur without hypoxemia, concurrent pulmonary pathology, or other pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
56
0
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 18 publications
9
56
0
10
Order By: Relevance
“…[2][3][4] The ultimate result of hydrocarbon aspiration is interstitial inflammation, intraalveolar hemorrhage and edema, hyperaemia, bronchial necrosis, and vascular necrosis. 5,6 The hemorrhagic alveolitis and bronchial and vascular necrosis can result in a hemorrhagic pleural effusion, which has been rarely reported. 7 Following poisoning, respiratory effects occur as a result of aspiration and ingestion leading to lipoid pneumonitis that increases the transpulmonary pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] The ultimate result of hydrocarbon aspiration is interstitial inflammation, intraalveolar hemorrhage and edema, hyperaemia, bronchial necrosis, and vascular necrosis. 5,6 The hemorrhagic alveolitis and bronchial and vascular necrosis can result in a hemorrhagic pleural effusion, which has been rarely reported. 7 Following poisoning, respiratory effects occur as a result of aspiration and ingestion leading to lipoid pneumonitis that increases the transpulmonary pressure.…”
Section: Discussionmentioning
confidence: 99%
“…n induced pneumothorax and empyema have been reported in literature but pyopneumothorax is a rare entity. 4,8 Lifshitz et al, 5 carried out a 4-year follow up study between 1995-1999 and reported that 118 (43%) out of 274 cases with hydrocarbon poisonings had pneumonia, hypoxia and fever; pneumonia was interstitial and bilateral; and it was associated with vomiting. 4 Pleurisy and pneumothorax were not reported in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 La alveolitis hemorrágica y la necrosis de los bronquios y vascular pueden causar derrame pleural hemorrágico, una situación raramente notificada. No se recomienda inducir el vómito en el tratamiento de la ingesta de derivados de hidrocarburos.…”
Section: Presentación De Un Casounclassified
“…Si aumenta la leucocitosis y se observan infiltrados y fiebre después de las primeras 24 a 48 horas, debe agregarse un tratamiento antibiótico debido al riesgo de neumonía bacteriana secundaria. [3][4][5][6][7][8][9][10] A nuestro paciente se le colocó una sonda de drenaje torácico por la presencia del neumotórax espontáneo y el derrame pleural. El paciente se recuperó satisfactoriamente después del tratamiento inicial con oxígeno inhalado, antibióticos, esteroides y salbutamol inhalados y tratamiento complementario, sin secuelas pulmonares residuales.…”
Section: Presentación De Un Casounclassified